2017
DOI: 10.1177/0731684416687041
|View full text |Cite
|
Sign up to set email alerts
|

Development of intimate contact during processing of carbon fiber reinforced Polyamide-6 tapes

Abstract: Contact development between the surfaces of two tapes is considered as a critical step in processing carbon fiber reinforced thermoplastic composites. In this study, the development of intimate contact between carbon fiber reinforced Polyamide-6 (PA-6) tapes is investigated experimentally using consolidation experiments and X-ray computed tomography for quantitative contact characterization. The experimental results indicate that the development of intimate contact occurs in the range of seconds even when temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Interlaminar voids have remained in the laminate due to the rapid lay-up. These voids form a void channel network [34,35], and allow for the early release of moisture, as can be seen in Fig. 11(c), and prevent pressure build-up.…”
Section: Influence Of Blank Consolidation Qualitymentioning
confidence: 99%
“…Interlaminar voids have remained in the laminate due to the rapid lay-up. These voids form a void channel network [34,35], and allow for the early release of moisture, as can be seen in Fig. 11(c), and prevent pressure build-up.…”
Section: Influence Of Blank Consolidation Qualitymentioning
confidence: 99%
“…In another approach, the evolution of the intimate contact during the consolidation was assessed by the change of the thermal contact resistance between the adjacent plies of a laminate. To monitor the evolution of this thermal contact resistance, Schaefer et al installed thermocouples between the adjacent layers in the middle of composite laminate (Schaefer et al, 2016(Schaefer et al, , 2017. With the temperature values measured by the thermocouples, the thermal diffusivities of initial prepreg and of final consolidated laminate were estimated.…”
Section: Introductionmentioning
confidence: 99%
“…172 Using surface profile measurements to directly obtain the surface parameters is a notable advantage to this model; however, since the fractal characteristics exhibited by the surface may not be necessarily true for all tape materials, this model may not be applied generally to all tape materials. 176 Yang and Pitchumani’s fractal model was used in different research works. 17,36,38,41,146,167,177…”
Section: Process Modelingmentioning
confidence: 99%
“…In an attempt to obtain a quantitative contact characterization, Schaefer et al 176 investigated experimentally the degree of intimate contact between CF-reinforced polyamide-6 (PA-6) tapes. They found that intimate contact develops within seconds when temperature is slightly above T m and applied pressure in the range of 1–4 kPa and that the model of Mantell and Springer as well as that of Yang and Pitchumani generally overestimate the time needed to reach full contact although the Mantell and Springer model is more conservative.…”
Section: Process Modelingmentioning
confidence: 99%
See 1 more Smart Citation